The Effect of Mesh Size on Mechanical and Thermal Properties of Bamboo Composites - Ziani Adriant; Yulianto Yulianto; Ralf Förster; Dede Lia Zariatin (University of Muhammadiyah Malang, 2019)
The application of styrofoam in food storage causes environmental contamination. The foam material is containing styrene that creates a dangerous risk in food storage. The objective of the research is to investigate the feasibility of using black bamboo-composite as a coolbox material. In this research, there was three sizes of meshing was manufactured which are mesh 40, 30 and 20. The materials were composed of 30% black bamboo fiber and 70% SHCP 2668 resin. Six side sheet plates of composite did assemble using adhesive bonding method into a box shape. Several tests were performed which are tensile test, compressive test, impact test, and thermal conductivity test according to ASTM D638, ASTM D6411, ASTM D6110, and ASTM C1004 respectively.Mesh size 40 has the highest tensile test, compressive test, and impact test was the value of 17,4 MPa, 54,13 MPa, 0,085 Joule/mm2 respectively. Mesh size 20 has the best thermal conductivity was the value of 7.36 W/m.oC. Coolbox testing on mesh 20, 30, 40 compared with the same dimensions was given box styrofoam with a temperature of -2 oC. The results of the coolbox composite test against mesh size 20 have slower ice cube melting compared to mesh 30 and 40.